"Rolling out" High‐Molecular‐Weight Proteins, which Contain Repeating Polypeptide Motif, by Using Rolling Circle Amplification. Issue 15 (4th September 2013) - Zheng, Yue; Sintim, Herman O.
<x xml:space="preserve">Abstract</x> Keep going round in circles: On a circular mRNA template and without an end in sight, E. coli ribosomes have no option but to keep on making a high‐molecular‐weight polypeptide with repeating units. In this Highlight, the recently published work by Abe and co‐workers on this topic is discussed.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>